Convergence of Agriculture and Energy: Implications for Research and Policy - Cassman, Kenneth; Eidman, Vernon; Simpson, Eugene (Council for Agricultural Science and Technology (CAST), 2006)
Recent dramatic increases in energy costs are having a direct bearing on all agricultural activities within the United States. This commentary discusses the use of energy in agriculture and the food industry in light of current federal and state policies. Energy production from bio-sources also is addressed.